Evaluation of sexual function in women at two stages of multiple sclerosis - Firdolas, Fatih; Ozan, Tunc; Onur, Rahmi; Bulut, Serpil; Orhan, Irfan (Springer, 2013)
In the present study, we aimed to evaluate the sexual function in patients with multiple sclerosis (MS) who were examined in two subgroups and compare the results to the control group with a validated questionnaire. A total of 23 consecutive female MS patients divided into groups with relapsing-remitting MS (RRMS) and secondary progressive MS (SPMS) and 45 healthy control subjects were included into the study. The inclusion criteria were as follows: Definite MS, age between 18 and 60 years and an Expanded Disability Status Scale (EDSS) score of < 8. The neurologic impairment, the disability and the independence of the patient, and cognitive performances were measured, and also the effect of MS is evaluated by EDSS. No statistically significant difference was found between two groups. FSFI scores in both groups were significantly lower than the control group. Domain scores for desire, arousal, orgasm, pain, lubrication and satisfaction measured between RRMS and SPMS patients showed no significant difference. Comparing each domain score for arousal, orgasm and satisfaction revealed significantly lower scores in RRMS and SPMS patients compared to control group. In this study, we detected statistically significant decrease in FSFI scores in two groups of MS compared to healthy controls. We could not define a difference in sexual function in different stages of MS in women and a statistically significant negative correlation between EDSS and FSFI scores in the two subgroups of MS.
Keywords: Multiple sclerosis; Female sexual dysfunction; Women health